Upaya Meningkatkan Peran Masyarakat Dalam Pencegahan Hipertensi Melalui Edukasi Kesehatan - Musta’in Musta’in; Ikrima Ikrima; Tri Yuniarti; Liss Dyah Dewi Arini; Saryadi Saryadi (STIKes Ibnu Sina Ajibarang, 2023)
High blood pressure is a serious health problem because it is a major risk factor for cardiovascular disease. Results of an interview with the head of Posyandu Sakura 9 RW. 01 Manang, Grogol, Sukoharjo shows that more than 70% of people suffer from hypertension. Therefore, socialization through health counseling programs is needed to increase the role of the community in the context of preventing hypertension. At Posyandu Sakura 9 RW. 01 Manang, Grogol, Sukoharjo, community service activities are expected to be able to improve health degrees optimally. Through understanding ways to prevent hypertension, for example in the consumption of healthy foods and physical activity correctly, and can improve people's knowledge, behavior, and attitudes about hypertension. The solutions offered to partners are ways to prevent hypertension through health counseling activities on hypertension, healthy cooking demonstrations in order to reduce excessive consumption of sugar, salt and fat, and healthy heart gymnastics activities to increase physical activity. The conclusion of this community service activity is that the elderly at the Sakura 9 Posyandu are very enthusiastic and give appreciation regarding very useful activities.